ADAPTASI BERBAGAI VARIETAS JAGUNG DENGAN DENSITAS BERBEDA PADA AKHIR MUSIM HUJAN DI JIMBARAN KABUPATEN BADUNG - I Gusti Ayu Mas Sri Agung (Bumi Lestari Journal of Environment, 2009)
The experiment was conducted in the field at dryland farming areas at Cengiling village, Jimbaran, district of South Kuta, Badung (50 m asl), from 9 March until 3 June 2008. The objective of the experiment was to study the effects of plant population on grain yield, and forage production of corn varieties, plantedat the end of rainiy season. A randomized complete block design was used in this experiment, in which treatments were arranged factorially. The treatments were plant population (71,428; 142,857; 214,284 and 285,712 plants ha-1 or one, two, three and four plants hole -1), and corn varieties (BISI-2, CPI-2, Srikandi Putih and Local Bukit). All treatments were replicated three times. Results of the experiment indicated that interaction effects between plant population and variety were significant on grain yield and straw quality of corn. Variety of Local Bukit at population of 285,712 plants ha-1 resulted in the highest grain yield at 12% moisture (9.39 t ha-1), and grain oven dry weight (6.28 t ha-1). ). That variety at that population gave higher forage crude protein (7.66%) than that given by variety CPI-2 but was not significantly different from that given by BISI-2 and Srikandi P. The variety of Local Bukit at that population also resulted in lower forage crude fiber (18.16%) than the value given by the other varieties. The highest population resulted in the highest fresh and oven dry weights (22.76 dan 14.36 t ha-1) of forage. Variety of Local Bukit and BISI-2 gave higher (12.39 and 14.01 t ha-1) oven dry weights than the other varieties. In this experiment the optimum plant population for maximum grain yield and quality of forage for each corn varieties had not been obtained.